KONTRIBUSI KOMPENSASI DAN JOB DESKRIPSI TERHADAP KINERJA KARYAWAN - Fikri (Faculty of Social and Political Science, 2019)
One effort that is deemed necessary is to always provide compensation and provide a clear job description so that it will improve employee performance which in turn can increase competitive advantage. The purpose of this study is to analyze and explain the contribution of giving compensation and determining the job description of employee performance. The location of the research was conducted at the Kusuma Agrowisata Hotel, where the selection was based on a study that in the field of tourism industry, the provision of compensation and the preparation of clear job descriptions greatly determine employee performance in particular and company performance in general. Statistical test results between compensation and employee performance obtained a significant value of 0,000. The significant value is still below 0.05, so the variable giving compensation affects the performance of employees. The positive regression coefficient value indicates that if compensation increases, the performance of Kusuma Agrowisata Hotel employees also increases. The level of compensation has a contribution to the value of the decline in employee performance by 0.488 with a proven strong / significant influence between providing compensation to employee performance, so of course this compensation must receive attention from both employees and the company. Job descriptions are a good means of combining talent and can provide innovative solutions to an established approach.